PENGARUH FIRM SIZE DAN GROWTH OPPORTUNITY TERHADAP FIRM VALUE MELALUI CASH HOLDING SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2018-2021 - Maulida, Yuni Astri Ayu; Sari, Lita Permata; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Technological developments The change in business world and the revolution of entrepreneurship have changed because of technological development. Companies now focus not only on profit, but also on appreciation. Technology has facilitated the transformation of small businesses into global businesses. This study aims at is analyzing and testing the effects of Firm size and Growth opportunity on Firm value through Cash holding as an intervening variable in food and beverage companies listed in the Indonesia Stock Exchange year 2018-2021. The population in this study were 21 food and beverages companies listed on the Indonesian Stock Exchange during the 2018 – 2021 period. The sampling technique was determined by purposive sampling. Data analysis and hypothesis testing in this study use Structural Equation – Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application shows that Firm size has a negative significant effect on Cash holding, Growth opportunity has a positive but not significant effect on Cash holding, Firm size has a negative but not significant effect on Firm value, Growth opportunity has a negative but not significant effect on Firm value and Cash holding have a negative but not significant effect on the Firm value. Meanwhile, the results of the indirect effect hypothesis test show the firm size variable has a positive but not significant effect on Firm value through Cash holding and Growth opportunity have a negative but not significant effect on Firm value through Cash holding.